A cost-effective fluorescence mini-microscope for biomedical applications12. Issue 18 (21st September 2015) - Zhang, Yu Shrike; Ribas, João; Nadhman, Akhtar; Aleman, Julio; Selimović, Šeila; Lesher-Perez, Sasha Cai; Wang, Ting; Manoharan, Vijayan; Shin, Su-Ryon; Damilano, Alessia; Annabi, Nasim; Dokmeci, Mehmet Remzi; et al.
<x xml:space="preserve">Abstract</x> A miniature microscope was designed and fabricated with built-in fluorescence capability for biomedical applications.